Trying on change – Trialability as a change moderator for sustainable travel behaviour. (May 2016) - Strömberg, Helena; Rexfelt, Oskar; Karlsson, I.C. MariAnne; Sochor, Jana
Abstract: Based on Rogers' diffusion of innovations theory and an in-depth analysis of two case studies regarding travel mode shift, the paper examines how to support people's adoption of new travel behaviour. A key element for encouraging adoption is enabling people to trial behaviour in order for them to embark on the travel behaviour change process. The analysis indicates that trials could be used as a strategic tool, but need to be carefully designed to help the participants through the different stages of the behaviour change process. Fundamental elements need to be considered, including recruitment principles, duration of the trial, and the type of support offered. The after trial set-up stands out as especially important to consider, as it affects the conditions for the changed behaviour to be maintained by the participants after the end of the trial.